Factors affecting probiotic adhesion in vitro and to skin keratinocytes - Lizardo, Mariana Valente Palla (2022)
Probiotics are defined as "live microorganisms, which when administrated in adequate amounts confer a health benefit in the host". Although its main application is the digestive system, over the last years several benefits that come from its topical use, have been investigated. Several studies have reported beneficial effects on different skin disorders such as atopic dermatitis, acne, eczema, psoriasis, wound healing, skin aging and reactive skin. Its main action is assigned to the inhibition of skin colonization by pathogens. In order to understand the factors that affect the probiotic adhesion to skin keratinocytes, firstly the growth of three probiotic strains was evaluated (Lactobacillus rhamnosus, Lactobacillus delbrueckii subsp. bulgaricus and Propioniferax innocua) in vitro in the presence of abiotic factors similar to those found in skin, namely UV radiation, temperature, pH, NaCl and fatty acids. Then invasion and adhesion assays were performed on the three probiotics, in the presence of pathogenic bacteria (Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli). For that, Cell Culture studies were performed with HaCaT cells, counting later the bacteria through plate counting method using the culture media de Man, Rogosa and Sharp (MRS) and Brain Heart Infusion (BHI), for probiotic and pathogenic bacteria, respectively. As a result, E. coli showed no capacity to invade the keratinocytes, presenting a non-significant viable bacterial count (0.47 ± 0.62 log CFU/mL, while P. aeruginosa (2.19 ± 0.65 log CFU/mL) and S. aureus (2.74 ± 0.40 log CFU/mL) revealed higher invasive bacterial cell values and in invasion tests without the presence of probiotics. In contrast, in the adhesion assays, a considerable number (4.64 ± 0.13 log CFU / mL) of adherent bacteria was obtained. This value is close to those obtained for the remaining pathogenic bacteria: 4.77 ± 0.28 and 5.18 ± 0.04 log CFU/mL for P. aeruginosa and S. aureus, respectively, indicating that the bacterium E. coli does not have the capacity to invade keratinocytes, but rather to adhere to them. The remaining pathogenic bacteria invaded the keratinocytes, although the probiotics of the genus Lactobacillus showed a higher value of viable bacteria in invasion tests alone, demonstrating that these probiotics are more effective in the invasion of HaCaT cells than P. aeruginosa or S. aureus; in these assays the probiotics L. rhamnosus and L. delbrueckii showed approximately 2 more logs of viable bacterial cells in the interior than the pathogenic bacteria. In pathogen adhesion, E. coli adhered less to cells in the presence of probiotics; in competition assay with P. innocua (less 1.96 log CFU/mL) and L. rhamnosus (less 1.77 log CFU/mL), and in substitution assays with all probiotics, while P. aeruginosa only showed vi reduced adhesion ability in competition assays with the bacteria P. innocua (less 1.39 log CFU/mL) and L. rhamnosus (less 1.41 log CFU/mL). Lastly, S. aureus showed reduced adhesion capacity in substitution experiments with L. rhamnosus (less 1.59 log CFU/mL) and competition with P. innocua (less 1.12 log CFU/mL). The mechanisms responsible for the adhesion of probiotics to keratinocytes were investigated, verifying that this may occur through carbohydrates or proteins, as was the case for S. aureus. In ex-vivo assays, using human skin equivalents, the bacterium S. aureus adhered less (1.35 log CFU/mL) in the presence of L. rhamnosus, whereas the probiotic adhered similarly in the model with the presence of the pathogen and without it. The macroscopic analysis showed improvements (tissue regeneration, less exudate and white halo less evident) in wound healing on the model infected by L. rhamnosus and S. aureus suggesting that the utilized probiotic may be benefic in wound healing, inhibiting S. aureus colonization.